Juridical Analysis of Patients’ Rights to Information Disease and Action Medical by Doctor in Hospital - Raden Mas Syauqi Annuri Sam Kusuma Patria; Sutarno; Adriano (Verdict: Journal of Law Science, 2022)
This study analyzed juridical analysis of patients’ rights to disease information and medical action by doctors in hospitals. The method used is a legal research method that aims to find solutions to legal issues and problems that arise from them. The results of the study show that the legal implications of regulating the right to information on diseases and medical actions given to patients by doctors in hospitals have an impact on the patient’s right to receive disease information openly and transparently from doctors related to diseases experienced by patients and patients have the right to be served maximally in obtaining medical treatment (Health services) by doctors at the hospital so that patients have the right to file claims if these rights are not fulfilled. Then, the presence of new health law, namely Law Number 36 of 2009, gives patients the right to refuse actions taken against themselves and to end treatment and care for their own responsibilities after obtaining clear information about their disease. In conclusion, the emergence of the Prita Mulyasari case was based on the non-fulfilment of the patient’s right to medical information. It was due to the absence of adequate and accurate communication between the doctor and the patient. Conflicts can be avoided if all parties, in this case, the doctor, patient and hospital, negotiate through deliberation and consensus by considering their respective rights and obligations.